A Systematic Review and Meta-Analysis of the Prevalence of Congenital Myopathy - Huang, Kun; Bi, Fang-Fang; Yang, Huan (Frontiers in Neurology, 2021)
Background: Congenital myopathy constitutes a heterogeneous group of orphan diseases that are mainly classified on the basis of muscle biopsy findings. This study aims to estimate the prevalence of congenital myopathy through a systematic review and meta-analysis of the literature. Methods: The PubMed, MEDLINE, Web of Science and Cochrane Library databases were searched for original research articles published in English prior to July 30, 2021. The quality of the included studies was assessed by a checklist adapted from STrengthening the Reporting of OBservational studies in Epidemiology (STROBE). To derive the pooled epidemiological prevalence estimates, a meta-analysis was performed using the random effects model. Heterogeneity was assessed using the Cochrane Q statistic as well as the I2 statistic. Results: A total of 11 studies were included in the systematic review and meta-analysis. Of the 11 studies included, 10 (90.9%) were considered medium-quality, one (9.1%) was considered low-quality, and no study was assessed as having a high overall quality. The pooled prevalence of congenital myopathy in the all-age population was 1.50 (95% CI, 0.93~2.06) per 100,000, while the prevalence in the child population was 2.73 (95% CI, 1.34~4.12) per 100,000. In the pediatric population, the prevalence among males was 2.92 (95% CI, -1.70~7.55) per 100,000, while the prevalence among females was 2.47 (95% CI, -1.67~6.61) per 100,000. The prevalence estimates of the all-age population per 100,000 were 0.20 (95% CI 0.10~0.35) for nemaline myopathy, 0.37 (95% CI 0.21~0.53) for core myopathy, 0.08 (95% CI -0.01~0.18) for centronuclear myopathy, 0.23 (95% CI 0.04~0.42) for congenital fiber-type disproportion myopathy and 0.34 (95% CI, 0.24~0.44) for unspecified congenital myopathies. In addition, the prevalence estimates of the pediatric population per 100,000 were 0.22 (95% CI 0.03~0.40) for nemaline myopathy, 0.46 (95% CI 0.03~0.90) for core myopathy, 0.44 (95% CI 0.03~0.84) for centronuclear myopathy, 0.25 (95% CI -0.05~0.54) for congenital fiber-type disproportion myopathy, and 2.63 (95% CI 1.64~3.62) for unspecified congenital myopathies. Conclusions: Accurate estimates of the prevalence of congenital myopathy are fundamental to supporting public health decision-making. The high heterogeneity and the lack of high-quality studies highlight the need to conduct higher-quality studies on orphan diseases.